LINKAGE BETWEEN INCOME DIVERSIFICATION AND ASSET OWNERSHIP IN RURAL HOUSEHOLDS OF YAYU WOREDA AND HURUMU WOREDA, OROMIA REGIONAL STATE, ETHIOPIA - Kajela, Mabiratu Dangia; Kumar Dara, D. Prem (International Journal of Research -GRANTHAALAYAH, 2019)
Rural households are engage in a variety of farm and non-farm activities based on initial assets endowments to diversify their income and cope with the risk of agricultural loss. This study was designed to assess linkage between income diversification and asset ownership among rural households in study area. Mult-stage sampling techniques were used to collect primary data from 237 farm households using semi-structured questionnaire. Descriptive statistics and econometric models were used to analyze the data. Tobit model was used to pinpoint factors that affect intensity of household income diversification and principal component analysis was used to index asset owned by households. The study shows that farm activities are the most important source of income for rural households in the study area contributing 90.92% of total households income with the remaining 9.08% originating from non-farm activities. A mean of income diversification index is 0.414(41.4%). Factors that affect intensity of household income diversification were: aggregate index of human capital, aggregate financial capital index and extension contact positively and membership in agricultural cooperative, sex of household heads and access to training negatively. In the study area generally, household asset ownership positively and significantly affected intensity of households income diversification and it has served as means for income diversification. Asset endowment needs to be considered by policy makers in the planning of agricultural and non-agricultural initiatives in the study area.